Early Post-Release Movements, Prey Preference and Habitat Selection of Reintroduced Cheetah (Acinonyx jubatus) in Liwonde National Park, Malawi - Sievert, Olivia (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScConsEcol)--Stellenbosch University, 2020.